Understanding sub-Saharan Africa's extreme poverty tragedy - Simplice Asongu; Sara Le Roux (African Governance and Development Institute (AGDI), 2018)
Motivated by a recent World Bank report on achieving of Millennium Development Goals which shows that poverty has been declining in all regions of the world with the exception of sub-Saharan Africa (SSA), this study puts some empirical structure to theoretical and qualitative studies on the reconciliation of the Beijing Model with the Washington Consensus. It tests the hypothesis that compared to middle income countries, low income countries would achieve more inclusive development by focusing on economic governance as opposed to political governance. The empirical evidence is based on interactive and non-interactive fixed effects regressions and 49 countries in SSA for the period 2000-2012. The findings confirm the investigated hypothesis. As the main policy implication, in order to address inclusive development challenges in the post-2015 development agenda in SSA, it would benefit low income countries in the sub-region to prioritise economic governance. Other theoretical and practical contributions are also discussed.
Keywords: D31; I10; I32; K40; O55; 330; Inclusive development; Middle Class; Governance; Sub-Saharan Africa; Beijing Model; Washington Consensus